CoFe2O4–ZnO NPs applied in microwave‐assisted tryptic digestion. (9th June 2016) - Nawaz, Mohd Imtiaz; Hasan, Nazim; Wu, Hui‐Fen
Abstract : Rationale: Phosphorylation is a post‐translational modification of proteins that plays very important role in a large number of biological processes. However, despite recent advancements in phosphoproteome research, large‐scale detection and characterization of phosphopeptides by mass spectrometry (MS) is still a challenging task due to the low abundance of phosphopeptides and sub‐stoichiometric nature of phosphorylation sites. On‐particle microwave‐assisted trypsin digestion of phosphoproteins and enrichment of phosphopeptides is an effective method for identification/characterization of phosphopeptides. Magnetic nanoparticles typically can absorb microwave radiation and generate heat in order to resolve complex phosphproteins and to enhance the digestion rate and capture the phosphopeptides on their modified surfaces. Methods: In this study, we used a cheap and efficient method for rapid microwave‐assisted tryptic digestion of phosphoproteins and simultaneous enrichment of phosphopeptides using CoFe2 O4 ‐ZnO magnetic nanoparticles. Using this technique, the digestion time of phosphoproteins can be reduced and the phosphopeptides can be quickly analyzed by matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOFMS). For the first time, we have applied CoFe2 O4 ‐ZnO magnetic nanoparticles for enrichment of phosphopeptides from standard phosphoproteins (β‐casein and ovalbumin), complex samples (human serum and egg white) and a protein mixture of β‐casein and BSA (1:100). Results: Our results demonstrate that the capture efficiency of CoFe2 O4 ‐ZnO nanoparticles for β‐casein and ovalbumin in MALDI‐TOFMS is very high (detection limits 0.2 fmol and 20 fmol, respectively). The CoFe2 O4 ‐ZnO nanoparticles have high affinity for phosphopeptide enrichment for β‐casein in complex mixtures with BSA at 1:10 and 1:100 molar ratios in the microwave within 30 s. Conclusions: Compared with other reported magnetic nanoparticles, the CoFe2 O4 ‐ZnO nanoparticles are easy to prepare and handle, and can save time in the phosphopeptide enrichment procedure, making these nanoparticle a good choice for highly sensitive phosphopeptide enrichment. Copyright © 2016 John Wiley & Sons, Ltd.